2022
DOI: 10.1108/tlo-01-2022-0011
|View full text |Cite
|
Sign up to set email alerts
|

The influence of transformational leadership on work engagement in the context of learning organization mediated by employees’ motivation

Abstract: Purpose This study aims to focus on determining the influence of transformational leadership on work engagement as mediated by employee motivation. Design/methodology/approach The research findings are based on a quantitative analysis of a survey of 443 full-time employees working in the Guangdong–Hong Kong–Macao Great Bay Area (GBA) of China. Findings The positive perception of transformational leadership from employees enables them to accomplish tasks beyond expectations. With the help of structural equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 46 publications
0
14
0
5
Order By: Relevance
“…The effects of transformational leadership on work engagement, mediated by motivation, were examined by Chen and Cuervo (2022). They examined whether and to what extent employees' perceptions of transformational leadership triggered their intrinsic motivation for work engagement.…”
Section: Sustainable Workforce In Teleworkingmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of transformational leadership on work engagement, mediated by motivation, were examined by Chen and Cuervo (2022). They examined whether and to what extent employees' perceptions of transformational leadership triggered their intrinsic motivation for work engagement.…”
Section: Sustainable Workforce In Teleworkingmentioning
confidence: 99%
“…Kuok, Chan, Kou, Kong, and Mac (2022) examined the effects of customer inclivity and surface acting on mental health in terms of emotional exhaustion and other outcomes. Finally, Chen and Cuervo (2022) examined the how transformational leadership triggers employee self-motivation and further stimulates their work engagement.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that green separation and organizational learning culture appear as the two most important factors for creating a sustainable organization in a circular economy. By conducting a survey with employees working in the private enterprises located in China's Greater Bay Area, Chen and Cuervo (2022) intend to find out how transformational leadership can influence work engagement mediated by employees' motivation in the context of learning organization. As suggested in earlier literature (Molodchik & Jardon, 2015;Imran, Ilyas, Aslam, & Rahman, 2016), employees' perceptions of transformational leadership influence their self-motivation toward work engagement, which in turn facilitate collaborative learning.…”
Section: Overview Of Contributions In This Special Issuementioning
confidence: 99%
“…Diverse organizations or businesses are attempting to enhance the performance of all parts of a corporation in an effort to ensure its longevity. Humans are the only resource capable of driving other resources, making human resources one of an organization's most significant assets [2].…”
Section: Introductionmentioning
confidence: 99%